Effects of school‐based mental health literacy education for secondary school students to be delivered by school teachers: A preliminary study. Issue 9 (1st July 2015) - Ojio, Yasutaka; Yonehara, Hiromi; Taneichi, Setsuko; Yamasaki, Syudo; Ando, Shuntaro; Togo, Fumiharu; Nishida, Atsushi; Sasaki, Tsukasa
<x xml:space="preserve">Abstract</x> Aims Improving knowledge and beliefs about mental health (or mental health literacy [MHL]) may promote appropriate help‐seeking by adolescents who are suffering from mental health problems. We developed a concise, school‐staff‐led MHL program and examined its effects. Methods The participants comprised 118 grade‐9 students (61 boys and 57 girls). The program consisted of two 50‐min sessions, and was given by a schoolteacher. The effects of the program were evaluated before, immediately after and 3 months after the program, using a self‐report questionnaire. Results Knowledge of mental health/illnesses and desirable behavior for help‐seeking were significantly improved immediately after (post‐test, P < 0.001, and P < 0.001, respectively) and 3 months after the program (3‐month follow up, P < 0.001 and P < 0.001, respectively), compared with the test before the delivery of the program (pre‐test, Wilcoxon signed rank test). Proportions of the correct diagnoses of vignette cases of major depression and schizophrenia were significantly (P < 0.001) elevated from 38.3% and 19.1% (pre‐test) to 94.7% and 93.6% (post‐test), and 91.5% and 86.2% (3‐month follow up). Intentions to seek help and to provide peers with help with mental health problems were also significantly (P < 0.001) elevated at post‐test and at 3 months compared with the pre‐test. Conclusions A concise, school‐staff‐led program may have a significant effect on the improvement of MHL in secondary school students.